ECM-based microfluidic gradient generator for tunable surface environment by interstitial flow - Shimizu, Azusa (Biomicrofluidics, 2020)
We present an extracellular matrix (ECM)-based gradient generator that provides a culture surface with continuous chemical concentration gradients created by interstitial flow. The gelatin-based microchannels harboring gradient generators and in-channel micromixers were rapidly fabricated by sacrificial molding of a 3D-printed water-soluble sacrificial mold. When fluorescent dye solutions were introduced into the channel, the micromixers enhanced mixing of two solutions joined at the junction. Moreover, the concentration gradients generated in the channel diffused to the culture surface of the device through the interstitial space facilitated by the porous nature of the ECM. To check the functionality of the gradient generator for investigating cellular responses to chemical factors, we demonstrated that human umbilical vein endothelial cells cultured on the surface shrunk in response to the concentration gradient of histamine generated by interstitial flow from the microchannel. We believe that our device could be useful for the basic biological study of the cellular response to chemical stimuli and for the in vitro platform in drug testing.